Asian Attitudes and Perceptions Toward Hospital-At-Home: A Cross-Sectional Study - Lai, Yi Feng; Lim, Yee Wei; Kuan, Win Sen; Goh, Joel; Soong, John Tshon Yit; Shorey, Shefaly; Ko, Stephanie Q. (Frontiers in Public Health, 2021)
Introduction Hospital-at-Home (HaH) programmes are well-established in Australia, Europe, and the United States. However, there is limited experience in Asia, where the hospital is traditionally seen as a safe and trusted space for healing. This cross-sectional study aimed to explore attitudes and perceptions among patients and caregivers in Singapore towards this care model. Methods A quantitative study design was adopted to collect data among patients and their caregivers from medical wards within two acute hospitals in Singapore. Using a series of closed-ended and open-ended questions, the investigator-administered survey aimed to explore barriers and facilitators determining patients and caregivers responses. The study questionnaire was pretested and validated. Data were summarised using descriptive statistics, and logistic regression was performed to determine key factors influencing patients’ decisions to enrol in such programmes. Results Survey responses were collected from 120 participants (101 patients, 19 caregivers; response rate: 76%), of which 87 respondents (72.5%) expressed willingness to try HaH if offered. Many respondents valued non-quantifiable programme benefits, including perceived gains in quality of life. Among them, reasons cited for acceptance included preference for the comfort of their home environment, presence of family members, and confidence towards remote monitoring modalities. Among respondents who were unwilling to accept HaH, a common reason indicated was stronger confidence towards hospital care. Discussion Most patients surveyed were open to having acute care delivered in their home environment, and concerns expressed may largely be addressed by operational considerations. The findings provide useful insights towards the planning of HaH programmes in Singapore.